Security issues on banking systems - Mohd Khairul Affendy Ahmad; Rayvieana Vera Rosalim; Leau Yu Beng; Tan Soo Fun (nternational Journal of Computer Science and Information Technologies, 2010)
Bank is one of the examples of institute that using Information Technology (IT) in its daily task to fulfill the organizations and customers’ need. Business transaction, money transfer, ATM, credit card, and loan are some tasks that were done every day. Customers’ personal information stored by the bank is also considered as private and should not be disclose to anybody with no authorization. Only legal staff and legal bank’s customer can operate any of the tasks. Thus, bank has its own system to ensure their transaction works the way it is and prevent any activity that could cause lost to the organization and its clients or customers. Whether like it or not, some irresponsible people are always exist to challenge the robustness of a banking system. Even an amateur that claimed themselves as a hacker could transfer a sum of money from other account to his or her account without noticed. Bank account hacking has caused millions dollar losses around the globe. How could this happen? Were there any obvious weaknesses in the banking system that make it easily expose to treat? This article would discuss about the intrusion of banking system. It is important to realize how the security aspects in a banking system can influence such illegal activities which are then led to a great lost to the financial institution. Some recommendations would be included in this article to help to reduce or prevent the intrusion in the future.